Bimolecular recombination in ambipolar organic field effect transistors - Charrier, Dimitri S. H.; Vries, T. de; Mathijssen, Simon G. J.; Geluk, E.-J.; Smits, E. C. P.; Kemerink, Martijn; Janssen, R. A. J. (Organic electronics, 2009)
In ambipolar organic field effect transistors (OFET) the shape of the channel potential is intimately related to the recombination zone width W, and hence to the electron-hole recombination strength. Experimentally, the recombination profile can be assessed by scanning Kelvin probe microscopy (SKPM). However, surface potentials as measured by SKPM are distorted due to spurious capacitive couplings. Here, we present a (de)convolution method with an experimentally calibrated transfer function to reconstruct the actual surface potential from a measured SKPM response and vice versa. Using this scheme, we find W=0.5μm for a nickel dithiolene OFET, which translates into a recombination rate that is two orders of magnitude below the value expected for Langevin recombination.